Immune Thrombocytopenia: Pathophysiologic and Clinical Update - Stasi, Roberto (Seminars in Thrombosis and Hemostasis, 2012)
Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by both reduced platelet survival and suppression of megakaryocyte and platelet development. It can either be primary or secondary to other autoimmune disorders, infections, vaccines, lymphoproliferative disorders, and drugs. Antibodies reacting against platelet glycoproteins are typical of ITP; these antibodies can mediate destruction of platelets by the monocyte–macrophage system as well as suppress megakaryocyte proliferation and maturation. Abnormalities of cell-mediated immunity are known to contribute to the pathologic process. Like many other autoimmune diseases, ITP has a T helper cell type 1 bias and a reduced activity of T-regulatory cells. Cytotoxic T cells may directly lyse platelets and possibly suppress megakaryopoiesis. Recent studies suggest that mesenchymal stem cells are dysfunctional in ITP and may contribute to an aberrant amplification of the autoimmune response. Significant advances in the treatment of chronic ITP have been witnessed in the past decade, first with the introduction of rituximab and more recently with the thrombopoietin-receptor agonists. While splenectomy is still considered the gold standard in this setting, effective medical therapy is now available for patients in whom surgery is not an option.
Keywords: immune thrombocytopenia; platelet autoantibodies; B cells; T cells; corticosteroids; splenectomy; thrombopoietin-receptor agonists